경산모의 분만통증 경험에 관한 연구 - 여정희; Yeo, Jung-Hee (여성건강간호학회지, 1999)
Pain is a complex perceptual experience that is profoundly influenced by a number of variables, differing in quality as well as in intensity. Therefore we need to understand the actual experience of multiparous women in order to provide basic information for nursing care. The purpose of the study is to explore the experience of labor pain. The data are collected through in-depth interviews of 17 multiparous women in city of Pusan from October 1998 to March 1999. The interviews were conducted 1-2 days after delivery in the admission room. Each interview lasted about 45 minutes on average. Subjects were interviewed one at a time. The interviews were recorded with the consent of the subject. Data were analyzed by means of Giorgi's Phenomenological analysis methods and categorized according to the similarities of its contents. The investigator read the data repeatedly to identify themes and categories. Six categories that were identified were : 1) pain 2) regret 3) acceptance 4) maturity 5) accomplishment 6) newness. Under these categories there were seventeen themes. I. Pain: 1) too dependent on others 2) too painful 3) fear or anxiety from previous painful experience 4) avoidance of pain 5) couldn't control the pain II. Regret : 1) spouse's absence 2) unprofessional attitude of the staff 3) ignorance of other's towards their pain III. Acceptance : 1) took the pain for granted 2) accepted the pain as fate 3) endured the pain IV. Maturity : 1) appreciated the value of life 2) apprehension of parent V. Accomplishment : 1)is over sense of accomplishment 2) grateful the pain VI. Newness : 1) experienced a new feeling 2) quickly forgot the pain. The results of the study will provide basic data for labor pain management.